Competitiveness and Determining Factors of Indonesian Tea Export Volume in the World Market - Hendi Nursodik; Siswanto Imam Santoso; Suryani Nurfadillah (HABITAT, 2021)
Indonesia is one of the world's tea exporters, but the decline in the volume and value of its exports to date continues to occur. This study aims to 1) analyze the production trend and export volume of Indonesian tea. 2) analyze Indonesian tea competitiveness in the International market compared to other exporter countries (China, India, Kenya, Sri Lanka, and Vietnam).Â  3) analyze the determining factors of Indonesia's tea export volume to 7 major destination countries (Malaysia, Russia, Pakistan, USA, Germany, Poland, and Australia). The analysis methods used are simple linear regression, Revealed Comparative Advantage (RCA), Trade Specialization Ratio (TSR), and data panel regression. The results showed that the production and volume of Indonesian tea export will decrease every year. Indonesian tea has a very strong comparative competitiveness, but still below India, Kenya, Sri Lanka, and Vietnam. Indonesia tends to be an exporter of tea to the international market at the stage of export expansion. Factors determining the volume of Indonesian export are Indonesian tea production, the population of importer countries, real GDP per capita of importer countries, level of trade openness of importer countries, and importer countries' inflation rate.